(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the association between pre-eclampsia and obesity in primigravida. Study Design: A Prospective cohort study. Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Bahawal Victoria Hospital, Bahawalpur Pakistan, from August 2022 to February 2023. Materials and Methods: A total of 64 primigravida (32 obese and 32 non-obese) and 18 to 35 years of age were analyzed. At the time of enrolment, socio-demographic and clinical characteristics of each woman were recorded. Females were divided into two groups (32 primigravida in each group). Obese primigravida contained those primigravida women who had BMI>30 kg/m2 and gestational age>20 weeks, and non-obese primigravida contained all primigravida with BMI≤30 kg/m2 and gestational age>20 weeks. All the patients were followed by the researchers until delivery, and the presence or absence of preeclampsia was noted. Results: In a total of 64 primigravida women, the mean age was 26.86±5.33 years (18 to 35 years) while 33 (51.56%) were between 18 to 25 years. Gestational age of 34 (53.1%) women were between 20-30 weeks. Place of living was rural among 33 (51.6%) women. In obese women, pre-eclampsia was found in 11 (34.4%) women as compared to 3 (9.4%) non-obese women with p-value of 0.031 and relative risk of 3.67 which was statistically significant Conclusion: The frequency of pre-eclampsia in obese primigravida is significantly higher compared to non-obese primigravida. Our study showed obesity as a risk factor for pre-eclampsia and positive association between body mass index and pre-eclampsia.